2008
DOI: 10.1007/s11418-007-0217-9
|View full text |Cite
|
Sign up to set email alerts
|

An efficient method of propagation of Podophyllum hexandrum: an endangered medicinal plant of the Western Himalayas under ex situ conditions

Abstract: This study shows an effective but simple method of conserving characterized populations and elite clones through vegetative propagation and genetic diversity through seeds in Podophyllum hexandrum (family Berberidaceae). Seed dormancy has been considered to be a major constraint in these seeds and most of the earlier reports recommended dormancy-breaking pretreatments such as chilling, gibberellic acid (GA(3)), etc. However, seeds of the 14 accessions that we tested exhibited no dormancy and hence did not requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…The highest amounts of PDT were recorded in the belowground parts of 2-year-old plants harvested during LGP. Although this amount is much lower than that of in situ plants, i.e., 1.2 versus 1.96 [12], the difference in yield can be easily met by producing a large number of plants using our earlier reported protocol [7]. Interestingly, the 3-yearold plants with maximum biomass of below-ground parts did not yield the highest amounts of PDT.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The highest amounts of PDT were recorded in the belowground parts of 2-year-old plants harvested during LGP. Although this amount is much lower than that of in situ plants, i.e., 1.2 versus 1.96 [12], the difference in yield can be easily met by producing a large number of plants using our earlier reported protocol [7]. Interestingly, the 3-yearold plants with maximum biomass of below-ground parts did not yield the highest amounts of PDT.…”
Section: Discussionmentioning
confidence: 84%
“…The plant avoids, rather than tolerates its harsh environmental conditions by strictly synchronizing its growth with seasonal variations in temperature [6]. It has also been shown that P. hexandrum can be grown ex situ at lower temperate altitudes [7]. However, its growth behavior, and the right age and time of harvesting the below-ground parts under ex situ conditions are yet to be identified.…”
Section: Introductionmentioning
confidence: 99%
“…The soil study (sand versus peat-perlite) was performed at both temperatures with 30 plants for each soil type. Sand and peat-perlite were previously described to be successful for P. hexandrum, respectively for the germination of seeds and in transplanting of rootlets into soil (Kharkwal et al 2008;Guo et al 2012). For statistical analysis, a factorial design was used with three factors: soil, temperature and time.…”
Section: Experimental Designmentioning
confidence: 99%
“…1 filter paper moistened with aqueous solution of phytohormones (250 lM: V/V) or water (for control) according to Sharma et al (2006) and Kharkwal et al (2008) in Petri plates at 20 ± 1°C for overnight. After that, the seeds were shifted on to filter papers (Whatman No.…”
Section: Seed Collection Hormone Treatments and Germinationmentioning
confidence: 99%
“…In Podophyllum, slow and delayed germination is due to the structural barriers around the embryo (Sreenivasulu et al 2009), or the absence of specific components required for radicle elongation or both. Earlier studies on Podophyllum seed germination reports that the GA enhances the germination by removing physiological, morphological, or morpho-physiological dormancy (Kandari et al 2007;Sharma et al 2006 andKharkwal et al 2008). In seeds, as an adaptive measure to sustain the unfavoring conditions, ABA induces and then maintains the dormancy which leads to the delayed germination (Bewley and Black 1994).…”
Section: Aba Inhibits and Ga Promotes The Seed Germination In Podophymentioning
confidence: 99%